Regards croisés sur le tutorat à l'université : quelle efficacité dans le contexte universitaire marocain ? - Hassna Barakate; Sondoss Ben Abid-Zarrouk; Abdelouahad Mabrour (Université de Provence, 2021)
This contribution, which results from a triangulation process, aims to reflect the effectiveness of tutorial practices through the eyes of the actors involved. It is more precisely a question of identifying the relationship that exists between the representations made by students (tutors and tutored) of tutoring and the effectiveness of this educational support in a Moroccan context. We were able to deduce, from this qualitative and quantitative survey conducted with nine tutors and 115 tutored students from the Faculty of Letters and Human Sciences at Ibn Zohr University, that the use of tutoring is a significant element in the success of newcomers. However, its image as a form of faction in terms of student perception constitutes a factor in the non-use of this aid to success in the Moroccan university context.